Quantitative analysis of methyl and propyl parabens in neonatal DBS using LC–MS/MS. (June 2016) - Yakkundi, Shirish; Mulla, Hussain; Pandya, Hitesh; Turner, Mark A; McElnay, James
Aim: Excipients are used to overcome the chemical, physical and microbiological challenges posed by developing formulated medicines. Both methyl and propyl paraben are commonly used in pediatric liquid formulations. There is no data on systemic exposure to parabens in neonates. The European Study of Neonatal Exposure to Excipients project has investigated this.Results & methodology: DBS sampling was used to collect opportunistic blood samples. Parabens were extracted from the DBS and analyzed using a validated LC–MS/MS assay.Discussion & conclusion: The above assay was applied to analyze neonatal DBS samples. The blood concentrations of parabens in neonates confirm systemic exposure to parabens following administration of routine medicines.